Penerapan Algoritma Recursive DFS dalam pembuatan Labirin Dinamis pada Game “Lingkaran Setan” dengan teknik Procedural Maze Generation - Raidah, Afiifah Zain (Maliki Interdisciplinary Journal, 2024)
This research explores the application of Procedural Maze Generation techniques in creating dynamic mazes for the game "Lingkaran Setan". Dynamic mazes are necessary to provide an engaging and challenging gameplay experience, ensuring constant variation in each game session. We use a Procedural Maze Generation algorithm to automatically create mazes with complex yet accessible structures, allowing players to explore the game environment uniquely each time the game starts. This research focuses on the integration of the Procedural Maze Generation algorithm with the game "Lingkaran Setan," resulting in dynamic and always challenging environments. Experimental results show that using this technique can enhance replayability and player satisfaction. Additionally, we measure the algorithm’s performance in terms of efficiency and maze-building speed to ensure a smooth gaming experience. The findings from this study contribute to a further understanding of the application of Procedural Maze Generation techniques in the context of video games, providing a foundation for developing more dynamic and engaging games in the future.